2016
DOI: 10.1149/2.0781609jes
|View full text |Cite
|
Sign up to set email alerts
|

Communication—Sol-Gel Synthesized Magnesium Vanadium Oxide, MgxV2O5· nH2O: The Role of Structural Mg2+on Battery Performance

Abstract: Magnesium intercalated vanadium oxide xerogels, Mg 0.1 V 2 O 5 ·2.35H 2 O and Mg 0.2 V 2 O 5 ·2.46H 2 O were synthesized using an ion removal sol gel strategy. X-ray diffraction indicated lamellar ordering with turbostratic character. X-ray absorption spectroscopy indicated greater distortion of the vanadium-oxygen coordination environment in Mg In this report, Mg x V 2 O 5 ·nH 2 O were prepared by subtracting cations from a crystalline metal vanadate as an alternative strategy in order to adjust the cation am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Va nadium oxides continue to receive substantial attention as possible Mg battery intercalation cathodes based on prior encouraging results,p rimarily with V 2 O 5 and particularly when water molecules are incorporated into the V 2 O 5 structure and/or in water-containing electrolytes.Y in et al [96] utilized as ol-gel/ion exchange process to synthesize Mg-intercalated vanadium oxide xerogels (Mg 0.1 V 2 O 5 ·x H 2 O where x = 2.35 and 2.46) and evaluated their performance in 0.5 m Mg(TFSI) 2 /0.5 m dipropylene glycol dimethyl ether/ acetonitrile.T he compound with x = 2.35 exhibited ar eversible capacity for Mg 2+ intercalation of about 140 mAh g À1 at adischarge voltage of about 3Vvs.Mg/Mg 2+ .T he structural Mg was found to remain in the material during cycling and all capacity was attributed to Mg 2+ intercalation/deintercalation. This interesting material should be evaluated using an electrolyte capable of reversible Mg anode electrochemistry, although migration of water molecules out of the cathode would be detrimental to the Mg electrode behavior.…”
Section: Transition Metal Oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Va nadium oxides continue to receive substantial attention as possible Mg battery intercalation cathodes based on prior encouraging results,p rimarily with V 2 O 5 and particularly when water molecules are incorporated into the V 2 O 5 structure and/or in water-containing electrolytes.Y in et al [96] utilized as ol-gel/ion exchange process to synthesize Mg-intercalated vanadium oxide xerogels (Mg 0.1 V 2 O 5 ·x H 2 O where x = 2.35 and 2.46) and evaluated their performance in 0.5 m Mg(TFSI) 2 /0.5 m dipropylene glycol dimethyl ether/ acetonitrile.T he compound with x = 2.35 exhibited ar eversible capacity for Mg 2+ intercalation of about 140 mAh g À1 at adischarge voltage of about 3Vvs.Mg/Mg 2+ .T he structural Mg was found to remain in the material during cycling and all capacity was attributed to Mg 2+ intercalation/deintercalation. This interesting material should be evaluated using an electrolyte capable of reversible Mg anode electrochemistry, although migration of water molecules out of the cathode would be detrimental to the Mg electrode behavior.…”
Section: Transition Metal Oxidesmentioning
confidence: 99%
“…Va nadium oxides continue to receive substantial attention as possible Mg battery intercalation cathodes based on prior encouraging results,p rimarily with V 2 O 5 and particularly when water molecules are incorporated into the V 2 O 5 structure and/or in water-containing electrolytes.Y in et al [96]…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Electrode materials with layered structures show significant potential as Mg-ion cathodes due to their ability to transport Mg-ions within the layers via different ion hopping mechanisms [27][28][29][30]. Among different types of layered metal oxides, vanadium pentoxide (V 2 O 5 ) has attracted a significant attention as a cathode material for Mg batteries [13,26,31,32]. Prior work has demonstrated that V 2 O 5 can reversibly insert and de-insert Mg-ions [13,26,33].…”
Section: Introductionmentioning
confidence: 99%
“…Crystalline V 2 O 5 evaluated with an electrolyte with low H 2 O levels exhibited very low Mg-ion capacities (~10-60 mAh g -1 ) [26]. V 2 O 5 gels can be synthesized via sol-gel chemistry from both inorganic and metal-organic precursors [31,34], and then dried under ambient conditions to form xerogels or supercritically dried to form aerogels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation